TEACHING ENGLISH WITH THE AID OF AI - Elyorjon Rahimov Rahmonqulovich (PEDAGOGS, 2024)
This research aim is to analyze an artificial intelligence platform that can be used in imparting education as well as evaluating student performance. This research was conducted with a qualitative method by conducting in-depth interviews and a literature study. The findings of this study shows that Artificial Intelligence technology can be used as a means of developing English learning for students. There have been several studies that support research results, that AI can be used to improve students’ English skills through applications, websites, Virtual Reality technology, and other AI-based learning and teaching systems. The limitation of this research is that it does not examine how far the role of AI in students’ English learning is. For further research, it is expected to test how far the role of AI is to improve students’ English skills, especially Universitas Airlangga students.